Fructose Dehydrogenase Electron Transfer Pathway in Bioelectrocatalytic Reactions. Issue 1 (3rd November 2017) - Kizling, Michal; Bilewicz, Renata
Abstract: We present kinetic and mechanistic studies of fructose oxidation by fructose dehydrogenase (FDH) using the electrochemical methods of stationary and rotating disk voltammetry. FDH was physically adsorbed on unmodified multiwalled carbon nanotubes (MWCNT) to study direct electron transfer (DET) parameters, and for comparison an MWCNT with an adsorbed pyrene derivative of naphthoquinone employed as the mediator in mediated electron transfer, MET, was also examined. Kinetic parameters, such as the number of electrons transferred, the turnover number, and the electron transfer rate constant, were calculated. Comparison of the non‐turnover and catalytic behaviour revealed the role of the heme c active site in the electron transfer of FDH. It was also shown that a mediator with a sufficiently low formal potential, such as the naphthoquinone, substitutes for the heme c site in the electron transfer to the electrode. The kinetic parameters of the processes proved that the application of the mediator results in an increase in the rate of fructose catalytic oxidation compared to that of the DET oxidation process. Abstract : Sweet as sugar : Kinetic and mechanistic studies are presented for fructose oxidation by fructose dehydrogenase (FDH) using the electrochemical methods of stationary and rotating disk voltammetry. Two different systems were evaluated considering direct electron transfer and using a mediator with suitable formal potential.